Estoque e fracionamento de carbono influenciado por sistemas de cultivo e culturas de cobertura em um experimento de longo tempo - Conte, Cassiano (2024)
The Sistema Plantio Direto (SPD) is important not only for its contribution to crop productivity, but also for its savings in the use of fossil fuels and greater carbon sequestration, contributing to improved soil quality and reduction of greenhouse gases, as long as its basic assumptions are respected (minimum and exclusive disturbance in the seeding line, crop rotation and permanent soil cover). In order to verify the influence of tillage systems and cover crops on the content and stock of Total Organic Carbon (COT), Particulate Organic Carbon (COP) and Mineral-Associated Organic Carbon (COAM) in the soil, an experiment located in the experimental area of UTFPR-PB, in the city of Pato Branco-PR, was evaluated. The experiment was installed in 2011 and consisted of a combination of three tillage systems (no-tillage - PD, minimum tillage - CM, and conventional tillage - PC) and three cover crops (black oat - AP, forage radish - NF, and hairy vetch - EP), under a randomized block design with three replications. In September 2022 and August 2023, dry matter production of cover crops was collected and evaluated. Samples were collected and evaluation of COT, COP, and COAM in the soil was carried out in October and November 2022, at a depth of 0-100 cm, divided into eight layers. In March 2023, soybean crop yield components were harvested and evaluated. Higher soybean yields were verified with PD. The dry matter production of cover crops was influenced by the species used, both in 2022 and in the accumulated total of both years, being higher in AP. The highest COT content was observed in the surface layers, without influence of the tillage systems, but affected by the cover crops, where EP showed the highest content in the 20-30 cm layer. There was an interaction between the tillage systems and cover crops for the COP content in the 0-5 cm layer, with the highest result in the NF in CM combination. In the 5-10 cm layer, EP showed the highest COP contents. The COT stock was higher in PC in the 10-20 cm layer and with EP in the 20-30 cm layer. In the accumulated layers 0-30 cm and 0-100 cm, there were no differences between the tillage systems, however, it was influenced by the cover crops, where in both depths the highest stock was also observed with EP. There were no differences between the tillage systems regarding the COAM, however, it was influenced by the cover crops in the 20-30 cm layer and in the accumulated 0-30 cm and 0-100 cm, with higher values for EP.